1995
DOI: 10.1007/bf01793860
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the detection ofBorrelia burgdorferi DNA in urine samples by polymerase chain reaction

Abstract: It is difficult in some cases to identify an infection caused by Borrelia burgdorferi and to monitor the effect of therapy. Seropositivity will persist even after successful treatment and therefore may suggest ongoing infection. For direct detection of B. burgdorferi DNA in human urine samples, the polymerase chain reaction (PCR) was evaluated. A published primer system was selected, which amplifies a 259 bp fragment from the gene encoding the 23S rRNA. The lower detection limit of the primer system was 10 fg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…In addition to reports summarized in Table 7, B. burgdorferi DNA was detected by PCR in blood (189), SF (140,165), CSF (101), and urine (52,79,105,155,189) of patients with LA. Maiwald et al (105) found that 11 of 15 patients with LA (1 with arthralgia and a typical history of a tick bite and EM, 9 with arthritis as a major symptom with other etiologies ruled out, and 5 with arthritis in combination with other manifestations) were reactive on tests of urine by a PCR that amplified a 259-bp fragment of the 23S rRNA gene (161).…”
Section: Patients With Joint Manifestationsmentioning
confidence: 90%
See 4 more Smart Citations
“…In addition to reports summarized in Table 7, B. burgdorferi DNA was detected by PCR in blood (189), SF (140,165), CSF (101), and urine (52,79,105,155,189) of patients with LA. Maiwald et al (105) found that 11 of 15 patients with LA (1 with arthralgia and a typical history of a tick bite and EM, 9 with arthritis as a major symptom with other etiologies ruled out, and 5 with arthritis in combination with other manifestations) were reactive on tests of urine by a PCR that amplified a 259-bp fragment of the 23S rRNA gene (161).…”
Section: Patients With Joint Manifestationsmentioning
confidence: 90%
“…Not surprisingly, procedures involving simpler methods have been developed; these include simple boiling of the specimen (88), centrifugation and boiling (31), alkali lysis (111), adsorption to coated or uncoated silica in the presence of chaotropic salts (7,21,51,68,105), boiling and concentration by centrifugation and ultrafiltration (128), and boiling in the presence of a cation exchanger (Chelex 100; Bio-Rad, Richmond, Calif.) (93). Although the mechanism by which Chelex improves the DNA extraction, is not known, it is thought to aid in stabilizing the DNA double helix (182).…”
Section: Sample Preparationmentioning
confidence: 99%
See 3 more Smart Citations